(untitled) (Research, Society and Development, 2023)
This research was conducted between the years 2019 and 2021 in the municipality of Solânea - Paraíba, in northeastern Brazil, located in Brazilian semi-arid region. The main goal was to measure the sustainability of family agro-ecosystems by identifying the key elements responsible for the performance of the studied farms. The research is based on mixed methods of the Sequential transformative strategy type. The theoretical-methodological framework was the Framework for Evaluation of Natural Resource Management Systems incorporating Sustainability Indicators [MESMIS] which based on systemic theory allows a multicriteria measurement using sustainability indicators. We analyzed 46 family farms and listed 27 indicators grouped into 5 attributes. It was observed that the farms who adopted the agroecological system achieved a better performance of sustainability in all its dimensions, indicating the potential of this system for family farming, especially in semi-arid and low-development regions. Environmental factors such as the extreme conditions of the semi-arid region - aggravated by global warming - and historical factors, such as an unequal land structure defined by violent conflicts and a panorama of low systemic development seriously compromised the sustainability of family farming in the semi-arid region of Paraíba.